The quest for personal power : transforming stress into strength - Nuernberger, Phil. (New dehli : Full circle, 2001)
Stress arises when we let fear & self-doubt control our thoughts & actions . . . when we fail to take charge of the power of the mind. Addresses the roots of our fears & offers solutions to the epidemic of stress. We must learn to use the power & potential of the mind to respond to outside pressures, to eliminate stress, & to achieve wellness & confidence. Reveals the causes of stress & explores the different dimensions of experience: the physical, psychological, & spiritual aspects of our identity. Shows what inner resources are available to us, & how we can have the skills to use them, so we can turn uncertainty into self-confidence, loneliness into self-reliance, & stress into strength.
Keywords: Self-control.; Self-perception.; Mind and body